Sustainable Waste Management Model in Bali: Integration of Public Policy and Local Wisdom - Ariati, Ni Kadek; Wirata, Gede; Astawa, I Wayan (Indonesian Association for Public Administration (IAPA), 2025)
Waste management is one of the most pressing environmental challenges in Bali, along with increasing tourism activities and population density. This research aims to analyze how local wisdom applied through customary instruments such as awig-awig and pararem can be integrated into public policies to create sustainable waste management. The method used is qualitative descriptive based on literature studies and secondary case studies that examine various customary-based waste management practices in Bali. Data were collected through the analysis of policy documents, activity reports, and previous research results, and analyzed using the Miles and Huberman models. This study found four main things: (1) the application of pararem and customary sanctions to increase community discipline in sorting and processing waste; (2) synergy between customary institutions and local governments through community-based management programs to strengthen the implementation of formal policies; (3) the values of Tri Hita Karana play a role as a moral foundation that fosters collective environmental awareness; and (4) collaboration between actors within the framework of collaborative governance encourages the formation of an adaptive and sustainable management system. Practically, this research provides an understanding of the importance of the role of indigenous villages in supporting local value-based waste management policies, while academically adding insight into the integration of local wisdom in public policies in the environmental sector.